Cropping system intensification for smallholder farmers in coastal zone of West Bengal, India: A socio-economic evaluation - Mandal, Subhasis; Sarangi, Sukanta Kumar; Mainuddin, M.; Mahanta, K. K.; Mandal, Uttam Kumar; Burman, D.; Digar, S.; Sharma, P. C.; Maji, B. (Frontiers in Sustainable Food Systems, 2022)
Introduction It is estimated that five out of six farms in the world are operating less than two hectares of land, called smallholder farmers, and they are producing over one third of the global food. Cropping system intensification research and interventions at farmers' fields could be one of the ways to improve the prevailing cropping systems. Understanding socio-economic issues are important for the successful implementation of improved or new cropping systems and for increasing farmers' income in the coastal zone of the Ganges delta. A socio-economic evaluation study was carried out to understand how far the suggested cropping options were feasible to smallholder farmers in the coastal zone; quantify the benefits due to the adoption of new cropping systems; how far those options were socio-economically suitable for the targeted smallholder farmers; and to identify the key factors that might be affecting the out-scaling of the evolved options to a larger group of farmers. Methods Baseline and endline surveys were conducted with 90 farmers before and after the demonstration of various cropping systems at farmers' fields. Techno-economic suitability of new crops and management options were evaluated through accounting benefits of adoption and identifying various constraints in adoption. Behavioral analysis was carried out to identify factors affecting large-scale adoption of the new/improved cropping systems evolved. Results and discussion The socio-economic survey quantified the increase in cropping intensity higher than the baseline level (123–142%) and reduced the rabi (winter/dry) season fallow area by 30–35%. The study identified farmers' preferred interventions were low-cost drip irrigation and mulching, zero-tillage (ZT) potato with straw mulching, improving soil quality with lime and green manuring, and vegetable-based cropping systems interventions. Although the economics of the evolved cropping systems were favorable, however, availability of freshwater stored in ponds/canals, and income from on and off-farm were the most important factors determining the adoption of new systems on a larger scale.